(untitled) - Goode, Diane; Durell, Ann. (New York, 1989)
Presents a collection of folk tales and songs from a variety of regions and ethnic groups in the United States.
Keywords: Juvenile literature; Folk-songs, English; United States; Folk songs, English; United States; Folk songs, English; United States; Juvenile literature; United States; United States; Tales; Folklore